Toward Swarm Coordination: Topology-Aware Inter-UAV Routing Optimization - Hong, Liang; Guo, Hongzhi; Liu, Jiajia; Zhang, Yanning (IEEE transactions on vehicular technology, 2020)
Swarm unmanned aerial vehicles (UAVs) is an approach to the coordination of multiple UAVs as a system, which has huge advantages on mission capabilities, such as cooperative search, border surveillance, and situation awareness. For better swarm coordination, a robust inter-UAV network, especially in ad hoc mode, is needed. Due to the dynamic nature of UAV networks owing to mobility and topology change, adapting routing quickly to topology changes is one of the key components of UAV networks. Based on investigating the relationship between the swarm formation control and the network topology, we propose a proactive topology-aware scheme to track the network topology change. Through simulations on Qualnet and real-world experiments with five quadrotors, the results confirmed that the proposed scheme reduces the average delay and improves routing performance significantly.